Complex transcatheter aortic valve replacement in aortic regurgitation and transcatheter mitral annuloplasty in severe dextrocardia. (12th March 2021) - Rudziński, Piotr Nikodem; Mach, Markus; Gross, Christoph; Andreas, Martin
Abstract: A 70-year-old female with symptomatic severe native aortic regurgitation, acquired dextrocardia, moderate-to-severe secondary mitral regurgitation and prohibitive surgical risk was admitted for transcatheter aortic valve replacement. A balloon-expendable Sapien 3 Ultra valve was implanted successfully. After 6 months, the patient remained symptomatic due to the concomitant moderate-to-severe secondary mitral regurgitation. Transcatheter mitral valve repair using a Carillon Mitral Contour System was performed resulting in a significant reduction of mitral regurgitation and uneventful follow-up. Most importantly, other transcatheter repair techniques would not have been feasible due to the impossible transoesophageal echocardiography guidance. This is the first case of transcatheter aortic valve replacement in a patient with native aortic regurgitation, acquired dextrocardia and severe aortic annulus malrotation using a balloon-expendable valve. Moreover, it is the first transcatheter mitral valve repair procedure using Carillon device performed by a cardiac surgeon.